Mental characteristics of All-Japan National Team judo athletes from the perspective of UK Test: analysis of high mental health and workload capability - Yokoyama, T.; Saito, M.; Uchimura, N.; Ishikawa, Y.; Yasui, C.; Funakoshi, M.; Higashiyama, A. (Association for the Scientific Studies on Judo, Kodokan, 2023)
The purpose of this research is to validate the two coaching principles and discover new insights by extracting and analyzing the UK psychodiagnostic test data of the All-Japan national team judo athletes, focusing on mental health and workload capability. Analyzing the high scores of mental health, it is evident that the All-Japan athletes have overall high levels of mental health. There are more male athletes that belong to the Iow/middle level groups compared to female athletes, so it is important to identify these groups and provide them with the necessary mental health support. For workload capability, we found that there is a high proportion of athletes with both high mental health and high mental energy. From this observation, it can be said that our hypothesis about the two coaching principles is validated. Although this research did not lead to discovery of new insights, we were able to confirm that majority of the All-Japan judo athletes belong to the high mental health and high workload capability group. The authors think the ability to sustain this high level of mental capability in our athletes will be the key to prowess of Japanese Judo on the world stage.